2축 자력계와 3축 자력계의 자기장 탐지성능 개선에 관한 연구 - Lim Byeong Seon (The Graduate School, Ajou University, 2015)
This dissertation is about performance improvement of magnetometers used as a part of detection system on conventional sea mines, which play important role in Korean defense and security. The proposed magnetometer is verified through the modeling and simulation process in advance. then, its performance is improved through practically manufactured with experimentation. It shall be applied to new underwater weapon systems. Since there is limitation in increasing detection performance of acoustic sensors which are commonly influenced by underwater operation environment, such as temperature, seabed materials, etc, magnetometers are used as an alternative solution for detection systems. Since after the cold war Korea is still remained as a divided nation, and still exposed to the threat of the underwater weapons system, such as 'The sink of Cheon-an(PCC) by the attack of the underwater weapon'. Deploying conventional mines in coastal area of hostile region has a risk factor. Our operation ship could be exposed to hostile surveillance systems. and our soldiers will be in danger. So, The national defense organizations in leading countries had been trying to develop mobile mines including CAPTOR(enCAPsulated TORpedo) which are combined at the propulsion part of torpedoes and warhead part of conventional mine. Our country where the threat of the underwater weapon systems like torpedoes continues, procurement of the new underwater weapon system like mobile mine is essential. Considering the development trend of leading mobile mine technology, it is necessary to upgrade conventional bi-axial magnetic sensors to 3-axis flux-gate sensors by introducing magnetometers. The biggest challenge in combining those two parts is that the ferromagnetic materials in propulsion systems can severely disturb magnetometers in main sensing component. So theoretical study is carried to investigate the effect of magnetic induction, permanent magnetization and magnetization induced by magnetostriction on the magnetometer performance. The non-magnetic instrument for magnetic field distribution measuring was made in order to measure the magnetic field distribution about the actually manufactured components and miniature combat ship and submarine by magnetic modeling were made for measuring their magnetic field using self-manufactured equipment with the moving mode. Based on these experiments, when the magnetometer of the conventional 2-axis was placed as the arbitrary rotation angle, the problem that is being generated in the magnetic field measurement was proved. Moreover, the some experiment was taken about the proposed 3-axis magnetometer. Firstly, conventionally, in the case of the used magnetometer, because of continuous power supply in order to secure the safety of the output characteristics, the battery capacity is the main problem for the mine system, especially for dropping or the Fire and Forget ones. A recently developed magnetometer proved that it can deliver equal or better performance than conventional one, while maintaining excellent stability and lower power consumption rate. Meanwhile, in the case of the traditional magnetometer, because of being comprised of the sensor of 2-axis, when it goes down to the bottom of sea by the dropping, the difference could not help being generated according to the bottoming positions. But, there are two methods to measure the magnetic field for 3-axis magnetometer. The first is that it measures the azimuth angle, the roll angle respect to bottom and the vertical and horizontal magnetic fields can be found with transformation of output coordinates. The second method is that it is possible to find the magnitude of magnetic field(total magnetic field) of the 3-axis magnetometer output, In the case of the latter, as simulated in the second chapter of this dissertation it is irrelevant of bottoming position and the detection capacity can be consistently maintained. Therefore, the second method is regarded as actually being the best. Also, the effect of the propulsion motor and actuator, where the ferromagnetic material used in mobile-mine, on the magnetic distortion for the magnetometer was tested. The detecting sensors including magnetometer, are mainly positioned in front part of a mine. Propulsion system including electric motors and actuators is usually placed in rear part, which is about 6 m away from the head where magnetometers are placed. In this case, the permanent magnetic components of the electric motor 9 nT and induced component gave 4.5 nT extent effect, and it was measured that the permanent magnetic components and induced magnetic component gave the effect in about 0.3 nT for actuators. Considering magnetic field component and daily varying capacity of the earth magnetic field in the case of the permanent magnetic components, there is no problem. And, in the case of the induced magnetic components, in case of assuming the change in the magnetic field by the tested object(warship or submarine) as 2,000 nTs, it did not have an effect on the response performance of main detection sensor just about 0.4 nTs. so, there is no magnetic field distortion by the propulsion electric motor, actuator and etc. Since it can be predicted that small amount(some nT) of magnetic field change by the permanent magnetic components of the rotor and encoder can not make the magnetic distortion. However, the screw (propeller) will be rotated by the sea current after bottoming of mobile-mine, we will need to verify through the experiment and some tests in sea.
학위논문(박사)--아주대학교 일반대학원 :NCW학과,2015. 2
Keywords: 무기체계